A spatial and temporal analysis of the gross motor response of an open skill with specific reference to 4-, 6-, and 8-year-old girls - Du Randt, R.(Rosina) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1981.